Investigation of breast pathologies in medical students and their families - Sousa, Bianca de Oliveira; Barbosa, Mariana Moraes; Santos, Anna Julia Martins dos; Cayres, Laura Bortolato; Motta, Lorena Lex da; Carneiro, Fernanda Kristina; Cicareli, Felipe Sá; Sá, Rafael da Silva (Mastology, 2024)
Introduction: Breast diseases include benign and malignant pathologies. However, during the differential diagnosis, it is important to distinguish benign pathology, precursor lesions of breast cancer, and malignant breast neoplasm. We believe that research among medical students on the prevalence of breast pathologies in this population and their families is important in addition to identifying patients at high familial risk for breast and/or ovarian cancer and awakening the interest of other medical students in this topic. The objective of this study was to analyze the prevalence of benign and malignant breast pathologies among medical students and their families. Methods: This is a quantitative analytical cross-sectional study. Female medical students over 18 years old were included in the study. Data collection was carried out using an online questionnaire. It was approved by the Research Ethics Committee under CAAE Protocol No. 51338121.0.0000.5515, and each participant consented through the free and informed consent form (TCLE). Results: A total of 303 medical students responded to the questionnaire and were included in the study. Around 13.5% of participants reported having had some breast pathology, 76.2% of which were cases of breast lumps. The average age of participants was 22.9 years (ranging between 18 and 53 years). The average age of family members at diagnosis (a sample of 69 women) was 57.1 years (ranging between 29 and 84 years). There was an association between the prevalence of breast pathologies and a family history of breast cancer (OR=1.712 [0.818; 3.585]). Conclusion: From the results, it appears that 13.5% of the participants had already been diagnosed with breast pathology, and 20.8% of these reported a family history of breast cancer. In this way, we can affirm the contribution of the study in the evaluation of screening criteria for breast and neoplasms and thus increase the detection rate and carry out early therapy.